COLLABORATIVE PEDAGOGY: WAYS TO IMPROVE THE EDUCATIONAL PROCESS - Radjabova Inobat Ravshanovna (Bright Mind Publishing, 2025)
This article examines the concept of collaborative pedagogy and its potential for enhancing educational processes. Through comprehensive literature analysis, the paper identifies key theoretical foundations, practical approaches, and implementation challenges in collaborative education. The findings suggest that collaborative pedagogy significantly improves student engagement, critical thinking, and knowledge retention when implemented systematically with appropriate structural support. This research contributes to the understanding of effective collaborative educational strategies and offers practical recommendations for educators and educational institutions.
Keywords: Collaborative pedagogy, educational improvement, educational process, collaborative learning, teaching methods, educational innovation.